2000
DOI: 10.1007/s005350070060
|View full text |Cite
|
Sign up to set email alerts
|

Increased response rate to interferon therapy after a second course in hepatitis C patients who show relapse after the initial course

Abstract: Some patients with chronic hepatitis C become HCV-RNA seronegative during interferon (IFN) therapy. However, about one-half of these patients show a relapse, evident by high serum alanine aminotransferase (ALT) level. In some patients with biochemical relapse, the serum HCV-RNA level becomes low immediately after the ALT relapse. Here, we assessed the changes in serum HCV-RNA level in patients with ALT relapse after IFN therapy, and evaluated the efficacy of a second course of IFN, started at the recovery stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…22 Moreover, we reported that HCV-RNA levels dropped dramatically following this "rebound phenomenon" in patients who exhibited "rebound" of ALT after completion of IFN therapy; we also reported that an increased response rate to IFN therapy was achieved after a second course in hepatitis patients who relapsed after the initial course of IFN therapy. 23 All three patients reported in this article exhibited an "autoimmune phenomenon," and the autoimmune reactions were activated by the administration of a low dose of IFN, resulting in acute exacerbation of hepatocellular impairment and elevation of total bilirubin. As a result, HCV-RNA levels dropped strikingly.…”
Section: Discussionmentioning
confidence: 89%
“…22 Moreover, we reported that HCV-RNA levels dropped dramatically following this "rebound phenomenon" in patients who exhibited "rebound" of ALT after completion of IFN therapy; we also reported that an increased response rate to IFN therapy was achieved after a second course in hepatitis patients who relapsed after the initial course of IFN therapy. 23 All three patients reported in this article exhibited an "autoimmune phenomenon," and the autoimmune reactions were activated by the administration of a low dose of IFN, resulting in acute exacerbation of hepatocellular impairment and elevation of total bilirubin. As a result, HCV-RNA levels dropped strikingly.…”
Section: Discussionmentioning
confidence: 89%
“…In the determination of predictive factors for IFN retreatment efficacy, simple logistic regression analysis was performed. Logistic analysis was performed for age (21-49 years versus 50-69 years), gender (male versus female), time of starting retreatment (Group A versus Group B), HCV-RNA level (<100 kcopies/ml versus ≥100 kcopies/ml), liver histology (HAI score 2-10 versus [11][12][13][14][15][16][17][18][19][20][21][22], and serum ALT value (< 2 × ULN versus ≥ 2 × ULN). Probability values of <0.05 stands for statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Our data supports that retreatment should be started after HCV recurrence as soon as possible for patients with low viral load. HCV load may rise from 4 to 8 weeks after completing treatment with IFN but then decrease [19]. Retreatment in Group A was probably started at a time of decreased HCV load, thus resulting in a high SR rate.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's low pretreatment HCV RNA concentration was probably a consequence of this CTL response. Arase et al 31 reported an increased response rate to a second course of IFN therapy that was started immediately after relapses following completion of the initial course of IFN. In their report, the serum HCV RNA concentration showed a decrease 2 to 4 weeks after the ALT peak.…”
Section: Discussionmentioning
confidence: 99%